(untitled) (Bangladesh Rice Journal, 2016)
CORRECTION: Due to a number of formatting and layout issues, the PDF of this paper was replaced on 10th October 2016. The page numbers of this article have changed from 94-96 to 99-101. The study aimed to isolate arsenic (As) oxidizing-reducing bacteria from As contaminated soil and water and to determine their ability to remove As from broth culture. Soil and water samples were collected from As contaminated area of BRRI farm, Bhanga, Faridpur. Arsenic oxidizing and reducing bacteria were isolated from the As contaminated soil (13 mg kg-1) and water (410 ?g/L) using spread plate count method in minimal salt (MS) medium after seven days of incubation. The oxidation activity of the bacteria as well as reclamation of As [III] was determined from NaAsO2 supplemented broth using atomic absorption spectrophotometer (AAS). The As-oxidizing bacteria population was present only in one soil sample, while in all water samples both oxidizing and reducing bacteria were present. A total of 36 As oxidizing-reducing bacteria were isolated. As-oxidizing bacteria removed 71-99% of applied As [III] in broth culture. Two out of 10 As-oxidizing bacterial strains appeared more efficient than others to remove As [III] under broth culture conditions. Bangladesh Rice j. 2015, 19(2): 99-100